Nitrates of cerium and samarium deposit on human enamel independently of a salivary pellicle - Louis Kopp; Karl-Anton Hiller; Fabian Cieplik; Arno Pfitzner; Florian Pielnhofer; Bastian Höfler; Christian Dolle; Áine M. Lennon; Sophia R. Bauer; Wolfgang Buchalla; Konstantin J. Scholz; Konstantin J. Scholz (Frontiers Media S.A., 2024)
ObjectivesThe aim of this study was to analyze the precipitation of Cerium(III)nitrate hexahydrate [Ce(NO3)3] or Samarium(III)nitrate hexahydrate [Sm(NO3)3] solutions on human enamel with and without a salivary pellicle. Investigated parameters were At%Ce and At%Sm measured using energy dispersive x-ray spectroscopy (EDX) after test solution (two concentrations) application.Materials and methodsPrecipitation of Ce(NO3)3 and Sm(NO3)3 solutions was examined on human enamel with and without a salivary pellicle. 6 enamel specimens each were obtained from 12 freshly extracted human third molars. These specimens were ground flat and polished. A salivary pellicle was created on 3 of the 6 specimens per tooth by storing the samples in human saliva. Subsequently, an aqueous solution of Ce(NO3)3 was applied to 2 of the 6 specimens (one with, one without salivary pellicle) for 60 s. The same was carried out with an aqueous solution of Sm(NO3)3 on 2 further specimens. The remaining 2 specimens from each tooth were treated with demineralized water (negative control). Ce(NO3)3 and Sm(NO3)3 solutions were applied at 25 or 50 wt% (aqueous solutions). The test materials and concentrations were distributed using a randomization table. After 60 s exposure and rinsing with demineralized water, the elemental composition (Ce, Sm, Ca, P, O, N, Na, Mg) of the enamel surface was analyzed by EDX. Atomic percentages (At%), differences (ΔAt%) and calcium/phosphorous-ratios (Ca/P-ratios) were calculated and analyzed non-parametrically (α = 0.05).Results2.0-2.3 At%Ce (median) was detected on Ce(NO3)3-treated enamel and 0.4-0.7 At% Sm (median) was detected on Sm(NO3)3-treated enamel. Ce was only detected on the surfaces after application of Ce(NO3)3, Sm only after application of Sm(NO3)3. The Ca/P-ratio was significantly lower (1.37-1.59; p = 0.028) after the application of 25% and 50%Ce(NO3)3 as well as 50%Sm(NO3)3 compared to the control treatment (demineralized water; 1.61-1.63). After treatment with Ce(NO3)3, At%Ca and At%Na were significantly lower (p ≤ 0.043) compared to treatment with Sm(NO3)3. No significant differences were found between specimens treated with 25% or 50% lanthanide nitrate solution. Presence of a salivary pellicle had no significant influence on the measured At% with the exception of specimens treated with 50% Sm(NO3)3 with increased At%Sm (p ≤ 0.046).ConclusionsCe(NO3)3 and Sm(NO3)3 precipitate on human enamel independently of the presence of a salivary pellicle.